USING DIFFERENT SCHEMES OF HOLSTEIN BRRED COWS’ SYNCHRONIZATION IN AGRICULTURAL LLC “PROMIN” OF MYKOLAIIV REGION - Bulayenko, A. U.; Zvenihorodska, T. V. (Scientific Progress & Innovations, 2019)
Increasing the profitability of dairy cattle breeding in Ukraine can be achieved by growing animal pro-ductive indices and reducing the cost for obtaining products. The effectiveness of dairy cattle breeding is closely connected with the intensity of herd reproduction. Embryonic mortality in cows is one of the reasons for the low effectiveness of artificial insemination. The loss of pregnancy during the embryonic period in highly productive herds reaches 40−55 %. For this reason our aim was to characterize the using of different synchronization schemes in agricultural LLC “Promin” of Arbuzyne district, Mykolaiiv region and find out the effectiveness of Ainil preparation impact on impregnation capacity of cows. The experiment was con-ducted on cows of Holstein breed from two to four years of age. Two experimental (n = 50 heads) and one control group (n = 50 heads) were studied to investigate the effect of non-steroidal anti-inflammatory Ainil (ketoprofen) preparation on impregnation capacity of cows. In the control group, the cows were inseminated without using any preparations. The scheme Double OvSynch was used on the cows of both experimental groups. On the 11th day after insemination, Ainil preparation was administered intramuscularly in the dose of 15 ml to the cows in the second experimental group. 15 ml of physiological solution were administered to the cows in the first experimental group. For the cows that were not impregnated, two ReSynch schemes were used: the standard scheme for the cows without gynecological pathology and modified scheme for the cows with cysts and two-sided hypo-ovaria. They were divided into two experimental groups (n = 15 head) and one control (n = 15 head), which were re-inseminated without using any preparations. Having analyzed the statistical data in the agricultural LLC “Promin” for 2018, it was determined that the birth rate of calves per 100 heads in case of using anti-inflammatory preparation Ainil was 88.3 %, while in case of using syn-chronization schemes without Ainil, the birth rate was 73.5 %, or 14.8 % less (p <0,01). Using the Ainil (ke-toprofen) preparation on the 11th day after the cows’ insemination and cows’ being synchronized according to the Double OvSynch scheme, increased fertility by 20 % as compared with the group of cows in case of spontaneous estrus and by 14 % as compared with the group of cows that were synchronized using the Dou-ble OvSynch scheme . It was found that using ReSynch schemes for the cows that were not impregnated from the first time, the impregnation capacity was15−33 % higher than in the control group (p <0.05).